Fatores associados à perda de implantes dentários e o impacto na qualidade de vida - Schimunda, Nathalia de Faria (2020)
Several factors can be associated with the loss of dental implants and this loss can affect the quality of life. The objective of this work was to evaluate the factors involved in the loss of dental implant as well as the impact of the loss on the individual's quality of life. This study included 25 patients who reported the loss of at least one dental implant. Personal data were collected, such as sex and education, and regarding the previous medical and dental history. Data such as medication use, presence of systemic diseases, smoking, and consumption of alcoholic beverages were noted. In the dental history, the items relevant to this study were whether patients installed dental implants and whether or not they were lost and how long after installation. To assess the quality of life in general, the WHOQOL-bref questionnaire was applied. The questionnaire to assess oral health-related quality of life was the Oral Health Impact Profile (OHIP-14). To assess the quality of sleep, the SAQ questionnaire (Sleep Assessment Questionnaire) was applied. The anxiety trait was assessed using the trait-state anxiety inventory (STAI T). Besides, the presence of dental crowding, incisal spacing, and anterior open bite were evaluated. The time elapsed between installation and implant loss was counted in months. The data were submitted to statistical analysis (Spearman, Mann-Whitney and Kruskal-Wallis correlation and Adjusted Generalized Linear Regression). Values of p <0.05 were considered significant. 25 patients participated in this study. There was no association between the factors and the time to implant loss (p> 0.05). The correlation test showed a significant moderate negative correlation between the Physical Domain of the WHOQOL-bref Questionnaire and Implant Loss Time in Months (r = -0.4689 p = 0.024). Patients with schooling up to high school lost their implants more quickly compared to patients with schooling up to higher education (β = -8.48; p = 0.047). When evaluating Implant Loss Time as an independent variable, no significant results were observed. We can conclude, within the limitations of this study, that the early loss of dental implants affects the general quality of life of individuals in the physical domain and this event is associated with the low level of school education.